Clustering the dominant defective patterns in semiconductor wafer maps - Taha, Kamal; Salah, Khaled; Yoo, Paul D. (IEEE, 2017)
Identifying defect patterns on wafers is crucial for understanding the root causes and for attributing such patterns to specific steps in the fabrication process. We propose in this paper a system called DDPfinder that clusters the patterns of defective chips on wafers based on their spatial dependence across wafer maps. Such clustering enables the identification of the dominant defect patterns. DDPfinder clusters chip defects based on how dominant are their spatial patterns across all wafer maps. A chip defect is considered dominant, if: (1) it has a systematic defect pattern arising from a specific assignable cause, and (2) it displays spatial dependence across a larger number of wafer maps when compared with other defects. The spatial dependence of a chip defect is determined based on the contiguity ratio of the defect pattern across wafer maps. DDPfinder uses the dominant chip defects to serve as seeds for clustering the patterns of defective chips. This clustering procedure allows process engineers to prioritize their investigation of chip defects based on the dominance status of their clusters. It allows them to pay more attention to the ongoing manufacturing processes that caused the dominant defects. We evaluated the quality and performance of DDPfinder by comparing it experimentally with eight existing clustering models. Results showed marked improvement.
Keywords: Clustering algorithyms; Semiconductor device modeling; Systematics; Partitioning algorithms; Fabrication; Manufacturing processes; Integrated circuits; Clustering of defective chips; Wafer defect patterns; Spatial autocorrelation; Wafer map